NFC/RFID sensor Tag for Wireless Temperature Monitoring in a Cold Chain - Nogues Estelle; Mackowiack Nicolas; Hamdoun Abdelaziz; Latrach Mohamed (E3S Web of Conferences, 2022)
This work presents the design and validation of a temperature sensor tag, which can be queried either by a cell phone using the NFC protocol or an HF RFID reader. It will easily ensure the cold chain failures and the product integrity. The proposed recording sensor can be placed on the packaging box to measure the temperature of the product. This allows to observe and store its evolution in order to guarantee the products quality and to respect the applicable provisions during transport. Thanks to a cell phone with the NFC, this recording data can be easily available, contrary to existing tags on the market. The design of tag is summed up as the choice of components, and the size of the antenna. Then a program for data recording and processing is developed using C language. Indeed, to have a triple gain of place, speed, and cost; an optimization of values recorded is operated. The overall tag size is 5.1x4x1.6 mm3, and its operation has been validated by performing in a real scenario: the temperature monitoring of a water bottle inside a bag for at least 50 minutes. The results of this test will be presented and discussed.